Strengthening consumer rights: the case for Lemon Laws in Malaysia’s automotive industry - Khadijah Mohd Najid,; Zati Ilham Abdul Manaf,; Muhammad Amrullah Drs Nasrul, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The prevalence of defective vehicles, or “lemons,” in the Malaysian automotive market continues to raise concerns despite the existence of consumer protection laws. This study aims to investigate the efficacy of Malaysia’s consumer protection laws in addressing this persistent issue and examine the potential impact of adopting Lemon Laws in Malaysia. Employing a doctrinal methodology, the study examines statutes, case laws, and scholarly literatures to offer a detailed understanding of the current legal landscape and the mechanics of Lemon Laws in selected jurisdictions. The research undertakes a comprehensive analysis of relevant legislation, including but not limited to the Malaysian Consumer Protection Act 1999 to identify potential limitations and areas for improvement. It further explores the concept of “Lemon Laws,” successfully implemented in various jurisdictions, and assesses their potential applicability within the Malaysian context. The research findings advocate for the strategic amendment of the existing Consumer Protection Act 1999 to incorporate provisions analogous to Lemon Laws, thereby strengthening consumer rights and nurturing a more equitable and transparent automotive marketplace in Malaysia.